GREEN INFRASTRUCTURE PLANNING: POTENTIAL SITES FOR NEW TDS 3R IN PANGKALAN KERINCI - Tsania, Tengku Annisa; Meidiana, Christia; Agustin, Imma Widyawasti (Journal of Environmental Engineering and Sustainable Technology, 2025)
The population growth and increasing domestic activities in Pangkalan Kerinci District have led to a significant rise in waste generation. However, the existing waste collection system remains inadequate, with only one Temporary Disposal Site (TDS) serving a limited area. This study, conducted from September 2024 to June 2025, employed a quantitative approach using both primary and secondary data. The analytical method applied was spatial overlay in a Geographic Information System (GIS), incorporating five variables: land availability, slope, road network accessibility, riverbank buffer zones, and settlement distance. The results indicate that although most areas meet the criteria for slope (98%), riverbank buffer zones (99%), and settlement distance (84%), only 556.03 hectares are classified as fully suitable when all criteria are overlaid, primarily due to limited land availability. These findings highlight the importance of integrated spatial planning in determining waste management facility locations and provide a reference for local governments to strengthen sustainable waste management infrastructure. The results further suggest the need for local government involvement in following up on this mapping with policies on land acquisition and the development of integrated TDS 3R facilities.